2008
DOI: 10.1590/s0066-782x2008001400009
|View full text |Cite
|
Sign up to set email alerts
|

Ressonância magnética vs cintilografia com pirofosfato marcado com tecnécio-99m para a detecção de necrose miocárdica perioperatória

Abstract: SummaryBackground: Perioperative myocardial infarction (POMI) is a complication of coronary artery bypass grafting (CABG) with a potential prognostic impact. Technetium-99m pyrophosphate myocardial scintigraphy (MS) is used in the diagnosis of POMI; however it shows a limited sensitivity for subendocardial lesions. Cardiovascular magnetic resonance imaging (CMRI), in turn, has a high accuracy in the detection of myocardial necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Cardiac magnetic resonance imaging is reported to be reliable for detecting perioperative small myocardial necrosis [8]. Rahimi and colleagues reported that revascularization-related hyper-enhancement was found in 32% of patients and predicted an adverse cardiac event after percutaneous coronary intervention or coronary artery bypass grafting [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging is reported to be reliable for detecting perioperative small myocardial necrosis [8]. Rahimi and colleagues reported that revascularization-related hyper-enhancement was found in 32% of patients and predicted an adverse cardiac event after percutaneous coronary intervention or coronary artery bypass grafting [9].…”
Section: Discussionmentioning
confidence: 99%
“…Considerando-se resultados já descritos por DANIEL et al (2008) e DANIEL (2009), referentes ao exame cintilográfico cardíaco em cães, assim como a enormidade de protocolos prontamente estabelecidos na Medicina Humana (WU et al, 2002;MONTE et al, 2008) e a escassez destes dentro da Medicina Veterinária, este trabalho destaca a importância de uma proposta para caracterização de um padrão normal de perfusão pulmonar em cães, preliminarmente da raça Rottweiller, mediante a cintilografia com vistas à identificação lesões pulmonares, por tromboembolismo, em seus estágios iniciais, auxiliando a prática clínica, assim como a resposta do paciente ao tratamento. A vantagem do método cintilográfico sobre a radiografia convencional, em relação ao diagnóstico do tromboembolismo ou embolismo pulmonar, está na avaliação funcional dos vasos pulmonares, e a utilização do [ 99m Tc](MAA) torna possível avaliar a característica vascular pulmonar quanto à presença de bloqueios do fluxo sanguíneo, que se apresenta como áreas homogêneas de cintilação ou como defeitos fotopênicos.…”
Section: Segundo Flückinger and Gomez (1984)unclassified